PCBs Contamination among Distribution Transformers in the Kathmandu Valley - Kattel, Ruska; Devkota, Bhupendra (International Journal of Environment, 2015)
Transformer is the crucial part in any electrical system, however there are many risks associated with its use. Thus this study was focused on assessing the status of PCBs contamination and distribution of transformers in Distribution Centre-North of the Kathmandu valley along with PCBs contamination in them. Each transformer within the study area was closely observed to obtain information about all transformers. The dielectric oil samples from the transformers were collected, safely stored and analyzed in Test Kits (L2000DX Chloride Analyzer System, recommended by UNEP). Among 111 samples of transformer oil analyzed, 4 transformers were found PCBs contaminated and they were manufactured before 1990s. The total amount of PCBs contaminated transformer oil in these transformers was 479.6 Kg. Seven transformers were found leaking, four transformers located at residential area were found emitting a low frequency tonal noise, two transformers were located within school compound, nine transformers were located near water body and around 1.44 square meters of soil surface was found contaminated by transformer oil. Though there is no way to eliminate all the risk and consequences of operating oil filled transformers, scientific distribution and proper handling could be the reasonable approaches to reduce the risks. DOI: http://dx.doi.org/10.3126/ije.v4i1.12175 International Journal of Environment Volume-4, Issue-1, Dec-Feb 2014/15, Page: 16-29